Tumour-infiltrating bystander CD8+ T cells activated by IL-15 contribute to tumour control in non-small cell lung cancer. Issue 8 (1st December 2021) - Leem, Galam; Jeon, Minwoo; Kim, Kun Woo; Jeong, Seongju; Choi, Seong Jin; Lee, Yong Joon; Kim, Eui-Soon; Lee, Jae-Ik; Ha, Seung Yeon; Park, Su-Hyung; Shim, Hyo Sup; Lee, Jin Gu; et al.
Abstract : Background: Tumour-unrelated, virus-specific bystander CD8 + T cells were recently shown to be abundant among tumour-infiltrating lymphocytes (TILs). However, their roles in tumour immunity have not been elucidated yet. Methods: We studied the characteristics of bystander CD8 + TILs from non-small cell lung cancer (NSCLC) tissues (N=66) and their activation by interleukin (IL)-15 to repurpose them for tumour immunotherapy. Results: We show that bystander CD8 + TILs specific to various viruses are present in human NSCLC tissues. We stimulated CD8 + TILs ex vivo using IL-15 without cognate antigens and found that IL-15 treatment upregulated NKG2D expression on CD8 + TILs, resulting in NKG2D-dependent production of interferon (IFN)-γ (p=0.0006). Finally, we tested whether IL-15 treatment can control tumour growth in a murine NSCLC model with or without a history of murine cytomegalovirus (MCMV) infection. IL-15 treatment reduced the number of tumour nodules in the lung only in mice with MCMV infection (p=0.0037). We confirmed that MCMV-specific bystander CD8 + TILs produced interferon (IFN)-γ after IL-15 treatment, and that IL-15 treatment in MCMV-infected mice upregulated tumour necrosis factor-α and IFN-γ responsive genes in tumour microenvironment. Conclusion: Thus, the study demonstrates that bystander CD8 + TILs can be repurposed by IL-15 for tumour immunotherapy.